A review on S-scheme and dual S-scheme heterojunctions for photocatalytic hydrogen evolution, water detoxification and CO2 reduction. (1st February 2023) - Kumar, Amit; Khosla, Atul; Kumar Sharma, Sunil; Dhiman, Pooja; Sharma, Gaurav; Gnanasekaran, Lalitha; Naushad, Mu.; Stadler, Florian J.
Graphical abstract: Highlights: Fundamentals of S-scheme and dual S-scheme have been discussed. Types of heterojunctions are elaborated with mechanism comparisons. Recent developments in synthetic methods and different morphology of S-scheme and dual S- schemes. S-scheme and dual S-scheme for photocatalytic environmental remediation and energy production. Bottlenecks, conclusion and future prospects discussed. Abstract: Discovering alternative materials and technologies that provide the meaningful potential to environmental and energy-related challenges in critical to the long-term viability of industrial activity and the evolution of society. Photocatalysts are undeniably important, and scientists are working hard to improve their photocatalytic performance. The high recombination rates of photogenerated electron-hole pairs as well as poor redox capability are addressed via heterojunction modification. In this direction, oxidation type and reduction type photocatalysts based S-scheme heterojunctions are highly promising owing to highly diminished recombination facilitated by internal electric field. This review has focused on the shift from Z-scheme to new revolutionary S-scheme based photocatalytic materials with high performance applications in the field of energy and environment. It can be concluded that controllable built-in electric field intensity and stable interfacial carrier transport process make S-scheme heterostrctures ideal. However their application is mainly limited to powder photocatalysts, don't apply to photo-chemistry and solar cells with external circuit, reaction thermodynamics and dynamics management in S-scheme photocatalysts is not adequate. To some extent, dual S-schemes address to these limitations and further research is to be carried out to fight the bottlenecks. Several perspectives on the future of S-scheme and dual S-scheme heterostructure were also provided based on rigorous review of the reported results. A discussion on the previously reported different types of heterojunctions and S-schemes is presented in this review along with plausible charge transfer mechanisms. The synthetic routes to S-scheme heterojunctions are also provided along with modifications and combinations. The current designing and perspective applications in numerous pollutant degradation, hydrogen production and CO2 conversion is selectively highlighted. The transition of mechanism elucidation from Z-scheme to S-scheme has been discussed with suitable case studies. However, S-scheme heterojunctions designing and fabrication is still new commercially and so present readiness and bottlenecks have been discussed. Hence it is quite imperative for a future roadmap to be laid to design and develop economically viable high performance S-scheme heterojunctions.